Adults with late diagnosed PKU and severe challenging behaviour: a randomised placebo-controlled trial of a phenylalanine-restricted diet. Issue 6 (9th February 2009) - Lee, P J; Amos, A; Robertson, L; Fitzgerald, B; Hoskin, R; Lilburn, M; Weetch, E; Murphy, G
Abstract : Background: Although early diagnosis and treatment in phenylketonuria (PKU) leads to excellent outcomes, a population of adults born before the introduction of newborn screening exists. They can have severe intellectual disabilities and behavioural problems, and are often dependent on full-time carers. Anecdotal evidence suggests that a diet that lowers blood phenylalanine concentration can have significant benefits upon behaviour. Methods: A prospective double-blind randomised placebo-controlled crossover trial of phenylalanine-restricted diet was performed in a group of 34 adults (aged 21–61 years, median 49) with late diagnosed PKU with severe challenging behaviour. Results: Only 17 completed the 60 week study: seven withdrew before the end of the baseline period; five withdrew during the first diet period; five withdrew during the second diet period (after moving into placebo phase). The mean (SD) blood phenylalanine was 1570 (222) μmol/l during baseline, 553(158) μmol/l during the active phase and 1444 (255) μmol/l during the placebo phase. In the 22 participants exposed to both active and placebo phases, no differences were demonstrated in behaviour assessed by the Aberrant Behavior Checklist and Vineland Adaptive Behavior Scales, behaviour diaries or on video analysis of direct observations. However, 76% of carers' comments were scored as positive during the active phase, compared with 54% during the placebo phase (χ 2 = 38.06, p<0.001). Conclusions: There are significant challenges in studying people with intellectual disabilities and considerable difficulties in instituting phenylalanine-restricted diet in this population. However, if attempted, there are potential benefits to quality of life for the individuals with PKU and their carers.